LEADERSHIP STYLE RIGHT IN THE DEMOCRATIC - Togu Harlen (Prosiding International conference on Information Technology and Business (ICITB), 2015)
Each leader has a leadership style that is different tobe adapted to the work environment so as to avoidinternal conflicts between superiors and subordinates.No leadership style that has been attached since theman was still in the womb, but some are derived fromexperience and knowledge about leadership.In an era of democratization takes leaders who have ademocratic leadership style that promotes democraticvalues that exist so that the subordinate was given theopportunity to cooperate and coordinate withcolleagues in the organization.Keywords: Style Leadership and Democracy.